Yarning quiet ways: Aboriginal carers' views on talking to youth about sexuality and relationships. (28th December 2017) - Vujcich, Daniel; Lyford, Marilyn; Bellottie, Chontarle; Bessarab, Dawn; Thompson, Sandra
Abstract: Issue addressed: Research suggests that young Indigenous people want carers to take a more active role in discussions about sexual health. The aim of this study was to ascertain carers' perspectives of: the importance of providing young people with information about sex and sexual health; what they want young people to know about sex and sexual health; and facilitators and barriers to discussing sex and sexual health with youth. Methods: Thirteen focus groups and three interviews were conducted with 81 carers in four rural and urban regions of Western Australia. Data were coded using a thematic approach, analysed using inductive Framework Analysis, and interpreted using the Aboriginal Family Wellbeing Model of Empowerment. Results: Many participants recognised the need for talking with young people about sex, and said they drew upon resources such as books, pamphlets and television and used humour to impart lessons. However, a large proportion of participants reported difficulties in educating youth about sex. Participants noted that colonisation had disrupted traditional structures for educating young people, and that sex was a challenging topic. The forced removal of children had interfered with Indigenous family structures and deprived some participants of the opportunity to acquire knowledge and skills from their own parents. Conclusions: Our findings emphasise the potential role of culture and empowerment in further improving outcomes related to relationships and sexual health. There is a need for more research into models of culturally‐empowering, family‐centred strategies for improving the sexual literacy of Indigenous youth.